Reporting of R&D Costs Under IAS 38 – The Case of Biopharmaceutical Companies - Markova, Maria; Hristov, Georgi (Research Papers, 2023)
The objective of the paper is to provide insights into the effects of IAS 38 on the financial information provided by companies operating in the biopharmaceutical industry, taking into account the increased expenditure on research and development activities during the COVID-19 pandemic. Financial reports for 2019 and 2020 of BioNTech SE (the company responsible for the development of one of the authorized COVID-19 vaccines) are analysed and given as an example for how the capitalization and expensing of R&D costs affect the information provided by entities. Example for improvement of the R&D accounting treatment is presented in the case of IFRS 6 “Exploration for and Evaluation of Mineral Resources”.
Keywords: Research and development costs; Intangible assets; Biopharmaceutical industry; Covid-19 vaccines; Accounting policy